Teori Koorientasi dan Acquired Needs Theory dalam merancang komunikasi internal BRI Life - Iroth, Yosie (Magister of Communication Science, Sahid University Jakarta., 2022)
Organizational Communication have become a critical aspect in today’s corporate world not because of digitalization speed and transformation but rather the lack of attention of organization to understand the social dynamic and communication dynamic that the leaders need to address in order to build a performance driven, motivated and engaged talents in the organization. A new model of organization communication need to be crafted by organizations due to the changes in the environment today this applies for PT Asuransi BRI Life. Adopting communication traditions, model and theories is a must while ensuring proper human resources practices are incorporated. Changes in the corporate culture due to younger workforce and new way of communication influenced by the new shareholder are among the few challenges need to be addressed. Leveraging the Acquired Need Theory with its three components of Need for Achievement, Need for Power and Need for Affiliation is an important foundation to this study in order to develop Internal Communication plan to establish a Co-Orientation Communication Theory